Hoop gloort. De renaissance van het gebouw van de Nederlandsch-Indische Kunstkring in Batavia (Jakarta) - Pauline K.M. van Roosmalen (Bulletin KNOB, 2005)
The Art-Society building in Batavia (Jakarta), which was opened in 1914, was designed by P.A.J. Moojen (1879-1955), one of the first professional architects working in the Dutch East Indies. Moojen, who received his training in Antwerp, was one of the founders of a contemporary Indonesian architecture and actively took part in the debate on style and architecture in the twenties.